Hybrid Stabilization of Thoracic Spine Fractures with Sublaminar Bands and Transpedicular Screws: Description of a Surgical Alternative and Review of the Literature - Marie-Therese Unterweger; Frank Kandziora; Klaus J. Schnake (Case Reports in Orthopedics)
Stabilization of unstable thoracic fractures with transpedicular screws is widely accepted. However, placement of transpedicular screws can cause complications, particularly in the thoracic spine with physiologically small pedicles. Hybrid stabilization, a combination of sublaminar bands and pedicle screws, might reduce the rate of misplaced screws and can be helpful in special anatomic circumstances, such as preexisting scoliosis and osteoporosis. We report about two patients suffering from unstable thoracic fractures, of T5 in one case and T3, T4, and T5 in the other case, with preexisting scoliosis and extremely small pedicles. Additionally, one patient had osteoporosis. Patients received hybrid stabilization with pedicle screws adjacent to the fractured vertebral bodies and sublaminar bands at the level above and below the pedicle screws. No complications occurred. Follow-up was 12 months with clinically uneventful postoperative courses. No signs of implant failure or loss of reduction could be detected. In patients with very small thoracic pedicles, scoliosis, and/or osteoporosis, hybrid stabilization with sublaminar bands and pedicle screws can be a viable alternative to long pedicle screw constructs.